STRATEGI PEMASARAN KOPI RIGIS (Studi Kasus di BUMDes Kampung Kopi, Pekon Rigis Jaya, Kecamatan Air Hitam, Kabupaten Lampung Barat) RIGIS COFFEE MARKETING STRATEGY (Case Study at BUMDes Kampung Kopi, Pekon Rigis Jaya, Air Hitam District, West Lampung Regency) - Sary, Linda Mareta; Al Rasyid, Harun; Indraningtyas, Lathifa; Utomo, Tanto Pratondo (Jurnal Agroindustri Berkelanjutan, 2024)
BUMDes Kampung Kopi is an agro-industry business that produces ground coffee under the Kopi Rigis brand. However, there are problems faced, namely the number of competitors between similar industries and the lack of promotion so that a marketing strategy is needed. The purpose of this research is to identify internal and external factors, formulate and determine the priority of Rigis Coffee marketing strategy. The method used in this research is descriptive method. Data analysis in this study uses the IFAS and EFAS matrix, the grand strategy matrix, the SWOT matrix, and the QSPM matrix. Based on the IFAS matrix analysis, it produces 5 strengths and 5 weaknesses with a total score difference of 0.43. Based on the EFAS matrix analysis, it produces 5 opportunity factors and 5 threat factors with a difference in the total score of 0.61, so based on the difference in the total scores of IFAS and EFAS it can be seen that the position of BUMDes Kampung Kopi is in quadrant I. The strategy that can be applied in this condition namely supporting an aggressive growth policy (growth oriented strategy). Based on the results of the formulation of the SWOT matrix, it produces 7 alternative strategies which will then be prioritized using the QSPM matrix. The QSPM matrix shows that the priority of marketing strategy is improving product quality by maximizing technological development, availability of raw materials, and market potential with a total TAS value of 6.09.Keywords: Coffee powder, marketing strategy, QSPM, SWOT